Pengaruh Atmosfer Toko, Citra Merek dan Kualitas Pelayanan Terhadap Minat Beli Ulang (Studi pada Starbucks Coffee Mall Citraland SC37) - Chalik, Muhammad Idham (Journal of Fundamental Management (JFM), 2024)
This study aims to analyze the effect of store atmosphere, brand image and service quality on repurchase intention. The population in this study are consumers who come to Starbucks Coffee Mall Citraland and have made a purchase transaction at least once. The sample used is 175 consumers, calculated using the Hair formula. Sampling method, with a g-form questionnaire research instrument. The methods of data analysis using Partial Least Square. This study proves that the store atmosphere has a positive and significant effect on repurchase intention. Brand image has a positive and significant effect on repurchase intention. And service quality has a positive and significant effect on repurchase intention.